Coronary artery disease and reasonably incomplete coronary revascularization in high‐risk patients undergoing transcatheter aortic valve implantation. Issue 1 (27th March 2019) - Saia, Francesco; Palmerini, Tullio; Compagnone, Miriam; Battistini, Paola; Moretti, Carolina; Taglieri, Nevio; Marcelli, Chiara; Bruno, Antonio G.; Ghetti, Gabriele; Corsini, Anna; Bacchi Reggiani, Maria‐Letizia; Marrozzini, Cinzia; et al.
Abstract: Objectives: To evaluate the long‐term impact of coronary artery disease (CAD) and heart team‐guided incomplete coronary revascularization in patients undergoing transcatheter aortic valve implantation (TAVI). Background: Revascularization strategy of CAD diagnosed with routine coronary angiography before TAVI is uncertain. Methods: Five hundred and forty consecutive TAVI patients were classified as having CAD or normal coronary arteries (no‐CAD). Within the CAD group, patients were further classified as those with complete (CR) versus incomplete revascularization (IR). Revascularization strategy was guided by the Heart Team following an algorithm largely based on current guidelines. Main outcome of interest was the incidence of 5‐year cardiovascular (CV) death. Results: Prevalence of CAD was 53.9%. CAD patients showed significantly lower left ventricular ejection fraction (LVEF: 55.8 ± 13.4% CAD vs. 61.4% ± 12.1 no‐CAD, p  < .0001), lower gradients, and larger ventricular volumes in comparison with the no‐CAD group. Within the CAD group, 138 patients (47.4%) received CR and 153 (52.6%) IR. In‐hospital mortality was 3.9%, without significant difference between groups (4.0% no‐CAD vs. 3.8% CAD, p  = .88; 2.9% CR vs. 4.6% IR, p  = .45). Median follow‐up was 57.8 months. Five‐year survival free from CV death was 79.6% in the CAD versus 77.9% in the no‐CAD group ( p  = .98), and 84.3% in the CR versus 74.3% in the IR groups ( p  = .25). These results were confirmed excluding patients with previous revascularization. At multivariable analyses, presentation with acute coronary syndrome (ACS) was significantly associated with 5‐year CV death. Conclusions: CAD is frequent in patients undergoing TAVI but portends an adverse prognosis only when presenting with ACS. Heart‐team directed complete or reasonably incomplete revascularization was associated with comparable outcomes.